The effect of nutrition education based on the Health Belief Model (HBM) on food intake in pregnant Afghan immigrant women: a semi-experimental study - Somaye Riazi; Vahid Ghavami; Seyyed Reza Sobhani; Nahid Jahani Shoorab; Kobra Mirzakhani (BMC, 2024)
Abstract Background According to the World Health Organization report, immigrants are at increased risk of malnutrition. Nutritional deficiencies in pregnancy are a public health concern and around 20 to 30 percent of pregnant women suffer from it worldwide. There has not been any investigation about the effect of any intervention on improving nutritional intake in pregnant Afghan immigrant women. Therefore, the present study was conducted to determine the effect of nutrition education based on the Health Belief Model (HBM) on food intake in pregnant Afghan immigrant women. Methods A semi-experimental study study was conducted on 116 Afghan immigrant pregnant women who have the inclusion criteria, were referred to health center No. 2 in Mashhad, Iran in June 2022 until February 2023, and were randomly assigned to the intervention (56) and control (56) groups. The demographic, HBM questionnaire and the standard 24-h food reminder questionnaire were the research tools. The intervention consisted of four sessions of 45-60 min of nutrition education based on the Health Belief Model in groups of 8-10 people. The questionnaires were completed before, immediately, and one month after the intervention by the research units. Data were analyzed with SPSS version 21 software. Results The intake of energy, protein, carbohydrates, and micronutrients such as iron, calcium, zinc, and vitamin D increased in the intervention group immediately and one month after the intervention significantly compared to before the intervention (P < 0.05). Although all these nutrients intake had a significant decrease in control group women (P < 0.05). Conclusions Nutrition education based on the health belief model is effective in the nutritional intake of Afghan immigrant pregnant women. According to the importance of getting enough nutrients in pregnancy and its effects on the mother and fetus's health, nutrition education based on the Health Belief Model model is suggested for these mothers. Trial registration It is registered in the Iranian clinical trials database under the code: IRCT20220629055312N1, Date of first registration: 25/07/2022.